Energy, poverty and development: A primer for the sustainable development goals - Hannah Goozee (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
The seventh goal of the Sustainable Development Goals (SDGs) is dedicated to ensuring access to affordable, reliable, sustainable and modern energy for all by 2030. While energy was implicit in the Millennium Development Goals (MDGs), the SDGs explicitly recognise the direct linkage between energy access and consumption and poverty and development. This evolution of the development agenda is closely related to an expanded understanding of poverty, as it moves beyond a monetary definition, to be seen as a more holistic measure of overall quality of life. Energy has thus become recognised as an important aspect of alleviating extreme poverty. However, what remains unclear is the impact that poverty reduction will have on worldwide energy consumption. There is a significant amount of literature concerning the connection between energy consumption-in particular electricity-and development, ranging from engineering modelling to development policy. Nevertheless, there is a lack of attention given to the direct causal relationship between poverty reduction and energy consumption. This paper reviews a variety of the current literature concerning energy and electricity consumption and poverty and development, to show that there is a need to directly address how poverty levels will shape future energy consumption. This relationship will have an impact on a number of issues critical to the achievement of the SDGs ranging from health to gender and the environment.
Keywords: 330; Energy; poverty; development; Sustainable Development Goals